Challenges and Solutions in Writing Legal Academic Papers in the Digital Age: A Perspective on Research Methodology and Sustainable Publication Practices - Muhammad Ruhunussa; Naek Efendi; Tugimin Harjotaruno; Supendi Supendi; Asep Mulyana (Jurnal Indonesia Sosial Sains, 2026)
The development of digital technology has changed the paradigm of writing and publishing legal scientific papers, including in data access, analysis techniques, and dissemination of research results. However, this transformation also raises various problems such as unclear legal research methodologies, low academic digital literacy, and an increased risk of scientific ethics violations such as plagiarism and misuse of artificial intelligence-based technology. This study uses a descriptive-analytical qualitative approach with normative legal research methods. Data was obtained through literature studies of scientific literature, academic journals, and related regulations, and supported by a conceptual approach to analyze the dynamics of legal research methodology and scientific publication practices in the digital era. The results of the study show that the main challenges include the lack of standardization of legal research methodologies, the limited ability of academics to utilize digital technology, and publication pressure that has an impact on the quality of scientific papers. In addition, the emergence of artificial intelligence technology poses new challenges in maintaining academic integrity. The proposed solutions include strengthening methodological capacity, integrating digital literacy in legal education, implementing technology-based academic ethics, and developing a transparent and sustainable scientific publication system.